Direct Arylation of C(sp2)–H Bonds in Anilines - Jacob, Clément; Annibaletto, Julien; Maes, Bert U. W.; Evano, Gwilherm (Synthesis, 2023)
Anilines selectively arylated at their ortho, meta or para positions are useful building blocks in synthesis and have found applications in many areas. The most straightforward method for their synthesis relies on the direct arylation of a C(sp2)–H bond of anilines, an attractive strategy avoiding the prefunctionalization of the starting anilines provided that such arylations proceed with high levels of regioselectivity. Such reactions are presented and discussed, in a comprehensive manner, in this review article, with an emphasis on the regioselectivity of the processes and factors governing both the reactivity and selectivity. 1 Introduction2 ortho-Arylation of Anilines2.1 Direct C(sp2)–H ortho-Arylation of Anilines2.2 Directed C(sp2)–H ortho-Arylation of Anilines3 meta-Arylation of Anilines4 para-Arylation of Anilines4.1 Direct C(sp2)–H para-Arylation of Anilines via Oxidative Radical Homodimerization4.2 Direct C(sp2)–H para-Arylation of Anilines via Transition-Metal Catalysis5 Conclusion and Outlook
Keywords: anilines; C–H arylation; regioselectivity; catalysis; directing groups